Relationships between Total Quality Management Critical Techniques in Automotive Industry - Amir, Azizi (2015)
The concept of Total Quality Management (TQM) was introduced in Japan and United States. Most of researchers have focused on soft TQM (principles and concepts) while some of them have concentrated on hard TQM (tools and techniques). More attention to TQM techniques has recently been applied in the manufacturing sector especially in automotive industry. This study proposes nine critical techniques as hard TQM for automotive industry. The purpose of this study was to identify the relationships between nine critical techniques of TQM. The relationships have been identified using opinions evaluation of 30 quality experts at 10 automotive factories in Malaysia through questionnaires and statistical analyses. Among the TQM critical techniques, SPC with FMEA, QFD with APQP, and QFD with FMEA have highest relationship degree. This study strongly recommends implementing the soft TQM along with the hard TQM using the results of this paper based on the importance and relationship level of nine critical techniques in order to have a more effective and efficient quality system.